Optical Simulations and Characterisations of Antenna Integrated YBCO THz Detectors - BERGFALK, AUREL (My University, 2014)
For accurate characterisation of quasi-optical terahertz (0.1 − 10THz) detectors the beam pattern of both the detector and the transmitter antennas have to be optically matched. For this purpose a quasi-optical waveguide has to be designed to couple the RF power from the source antenna to the detector. This can be done using focusing elements such as lenses or mirrors. In this thesis the beam patterns from different hybrid antennas (planar antenna on a Si lens) are simulated using CST Microwave Studio and a quasi-optical waveguide with two parabolic mirrors is designed. It is shown that it is possible with standard desktop computers to simulate the whole hybrid antenna for frequencies in the lower terahertz region. It was discovered that a quasi-optical waveguide designed using parabolic mirror was more sensitive to misalignment than expected. The standing waves in the system were also more present than expected making the alignment even more difficult. The coupling loss through the diagonal horns and the quasi-optical waveguide relative to direct connection withWR-2.2 interface were measured to be 1.3 dB at 452GHz and 1.5 dB at 389GHz. Responsivity measurements on a YBCO bolometer with a log-spiral planar feed antenna mounted on a ? = 5mm lens were also performed. The measurements gave an optical responsivity of 30 V/W at 452 GHz and 40 V/W at 389GHz. The bolometer used had an electrical responsivity of 50 V/W and was biased at 0.7mA.
Keywords: Informations- och kommunikationsteknik; Elektroteknik och elektronik; Information & Communication Technology; Electrical Engineering, Electronic Engineering, Information Engineering